Mechanical and Morphological Characterization Analysis on Aegle marmelos Dispersed Fiber-Reinforced Polymer Composite - Arul Jeya Kumar Arputham; Selwyn Jebadurai Devaraj; Manivanan Usaladi; Queen Alice Arulraj (Journal of Natural Fibers, 2023)
This research is a study on the mechanical behavior of novel natural composites consisting of Aegle marmelos fruit resin and epoxy resin as matrix, basalt mat fibers, and Aegle fruit shell powder as reinforcement and fillers, respectively. The composites were fabricated using a hand-lay molding process having five layers of basalt mat fiber and Aegle marmelos shell powder with epoxy/Aegle resins as a matrix. Five weight fraction samples were fabricated, namely EB (basalt and epoxy), EBAP (basalt, epoxy, and Aegle shell Powder), EBAR1 (basalt, epoxy, and 100 g of Aegle resin), EBAR2 (basalt, epoxy, and 150-g Aegle resin), and EBARP (basalt, epoxy, 100 g of Aegle resin, and Aegle shell Powder). The specimens of ASTM standards for various tests were prepared using a water jet cutting process. The specimens were subjected to tensile, flexural, and impact testing. The EBARP composite showed better tensile, flexural, and impact strength, compared to other composites. The composites were subjected to FTIR analysis to understand the existence of bonds in the resin. 1,3-butadiene, vitamin A, and ethylene were noted in the FTIR analysis. Scanning electron microscopy images of the composites revealed strong bonding between the fiber and the matrices.